Specifics of using diode lasers on different skin and hair types - Chernychko, Viktoriia (Global Prosperity, 2025)
Abstract. The article is devoted to the analysis of modern laser hair removal technologies with an emphasis on diode lasers, their wavelength and effect on different skin and hair types. The purpose of the article is to describe the features of the technology of using diode lasers for hair removal on different skin types. During the scientific research, general scientific methods of cognition were used: analysis, synthesis, induction, deduction, systematization, comparison, generalization and modeling. The results of the study show that the key mechanism of action of laser hair removal remains the principle of selective photothermolysis, in which light energy of a certain wavelength is selectively absorbed by melanin in the hair follicle, causing its thermal damage with minimal impact on surrounding tissues. Diode lasers with a wavelength of 800-810 nm have been shown to be the most versatile in clinical practice, as they combine high efficacy with a good safety profile for patients with skin phototypes III-V. Special attention is paid to three-wave diode systems (810+940+1060 nm), which provide more uniform heating of the follicle, minimizing the risks of overheating the epidermis, especially in patients with dark skin. It has been shown that wavelengths of 940 and 1060 nm are characterized by reduced melanin absorption in the epidermis and better penetration into the deeper layers of the dermis, which makes them effective and safe for phototypes IV-VI. In clinical conditions, these systems have demonstrated high efficacy, reducing hair density by up to 66% even on thin or poorly pigmented hair. It is concluded that diode lasers are the modern standard in the field of laser hair removal, due to the flexibility of settings, clinical effectiveness and high safety profile for different skin types. The use of combined wavelengths enhances the therapeutic effect and allows for an individual approach to the patient. The practical significance of the study is to provide scientifically based recommendations for the safe and effective use of diode lasers for hair removal, taking into account the skin phototype and hair structure.